In vitro and in vivo studies of cardiovascular disturbance following envenomation by Malayan Krait (Bungarus Candidus) - Chaisakul, Janeyuth; Chanhome, Lawan; Ahmad Rusmili, Muhamad Rusdi (2017)
Snake envenoming is a serious health problem that affect the population of developing and underdeveloped countries, causing morbidity and mortality. Malayan krait (Bungarus candidus) is an elapid species found in Southeast Asia. The venom contains highly potent neurotoxins that inhibit neurotransmission at the neuromuscular junction. Interestingly, cardiovascular symptoms such as hyponatraemia and blood pressure irregularities which not related to the known neuromuscular blockade activity of the venom have been reported in some victims. However, potential mechanism behind these cardiovascular symptoms has yet to be identified. The understanding mechanism of this cardiovascular disturbance would enable the clinical to anticipate the clinical prognosis and design a better management for Malayan krait envenoming treatment. Methods In this study, we have examined the cardiovascular effects of Bungarus candidus venoms from northeastern (BC-NE) and southern (BC-S) parts of Thailand using anaesthetized rat and isolated rat thoracic aorta preparation. Results A comparison of the reverse-phase-HPLC profiles of both venoms showed some differences with peak elution times. BC-NE and BC-S (50-100 μg/kg, i.v.) produced a significant dose-dependent hypotensive response in anaesthetized rats which was abolished by prior administrations of hexamethonium (10 mg/kg, i.v.) and recommended dose of Malayan krait monovalent antivenom. BC-NE and BC-S (3-100 μg/ml) also caused endothelium-dependent relaxation in isolated rat aortic rings. The pre-incubation of L-NAME (0.2 mM) prior to the addition of venom attenuated the aortic relaxation effect, suggesting the involvement of endothelium derived nitric oxide. Conclusion These finding indicate that the cardiovascular disturbance observed after envenoming by Malayan krait may involve autonomic reflex and vascular nitric oxide mechanisms.